In vitro studies of 7-dehydrocholesterol reductase (DHCR7) activity - Hämäläinen, Anna (My University, 2023)
Cholesterol is a crucial sterol found in membranes of animal tissues. It has many important endogenous roles, including acting as a structural component, taking part in membrane fusion, and as a biosynthetic precursor. It is also involved in hedgehog signaling. Thus, cholesterol is vital throughout human life. In humans, 7-dehydrocholesterol reductase (DHCR7) forms cholesterol and desmosterol. A malfunctioning DHCR7 may be fatal for fetuses. DHCR7 can be unintentionally inhibited by different drugs, which may thus act as teratogens when women are exposed to them during pregnancy. There is a limited amount of experimental information about such compounds. Thus, screening for DHCR7 inhibition during drug development could help detect potentially teratogenic drugs. This study aimed to (1) characterize and assess the suitability of human hepatic subcellular fractions for in vitro activity measurements of DHCR7, and to (2) carry out a preliminary inhibition screening of pharmaceutical compounds, which are known/suspected DHCR7 inhibitors. For this purpose, we used commercially available hepatic subcellular fractions together with thin-layer chromatography and liquid chromatography-tandem mass spectrometry methods. Unexpectedly, the subcellular matrices tested contained cholesterol, making it difficult to study the intended marker reaction. However, our data showed that the desmosterol-forming reaction could be used for DHCR7 activity measurements. Of the tested DHCR7 inhibitors, azaperone, mirabegron and trazodone inhibited DHCR7 when observing desmosterol levels. In summary, we were able to demonstrate DHCR7 activity and inhibition in human liver microsomes. However, more sensitive methods need to be developed for further analysis of DHCR7 inhibition.
Keywords: DHCR7, SLOS, cholesterol deficiency, cholesterol synthesis, drug development, enzyme inhibition, pregnancy, subcellular fractions, teratogenicity